Electrochemical Reduction of Manganese Mediated by Carbon Nanotubes/Li+ Modified Glassy Carbon Electrodes - Tan, W.; Radhi, M.; Ab Rahman, M.; Kassim, A. (Asian Journal of Chemistry, 2011)
Glassy carbon electrodes (GCE) were modified with carbon nanotubes (CNT) with and without Li+ dopant by a mechanical attachment method. These modified working electrodes, abbreviated as CNT/Li+/GCE and CNT/GCE, produced two reduction peaks of Mn(II) at +0.8 V and +0.1 V vs Ag/AgCl in 0.1 M KCl, which appeared irreversible during cyclic voltammetry. The sensing characteristics of the modified film electrodes demonstrated in this study were composed of: (i) a wide working potential window ranging from +1.8 V to -1.8 V (depending on different scan rates, pH, concentration and temperature); (ii) a wide applicable pH range (from at least 2-10); (iii) a wide applicable temperature range from 5-90 ºC; (iv) a current response that is stable and fast with a satisfactory and reproducible linear voltammetric and amperometric response to various analytes; (v) a good reproducibility and recovery rate in seawater and blood; (vi) interfering metal ions such as Hg2+, Cd2+ and Cu2+ appeared to pose positive interference on the reduction peaks of Mn2+. The reduction current of Mn2+ using CNT/Li+/GCE was largely influenced by concentration, pH, temperature and scan rate. Based on the calibration curve obtained, a linear graph of up to 1 mM Mn(II), with an impressive sensitivity response of 66.7 μA/mM, was obtained. Based on chronoamperometry, a diffusion coefficient for Mn2+ of 1.53 × 10-7 cm2/s was determined.